Impact study of regulator cum bridges - AJAY GOKUL A. J PRAVEENA N RAKHI J. F; Dr. Abdul Hakkim V. M (Guide) (Tavanur 2013 Department of Land and Water Resources & Conservation EngineeringKelappaji College of Agricultural Engineering and Technology)
Impact study of regulator cum bridges
Impact study of regulator cum bridges